A Dietary Supplement Based on Vegetable Oil Enriched With Altai Wapiti Velvet Antlers and Having Specific Functional Properties - Valery Petrovich Sergun; Darya Dmitrievna Ageenko; Valeriy Mikhailovich Poznyakovsky; Galina Cherentsova; Boisjoni Tokhiriyon (International Journal of Medical Toxicology and Legal Medicine, 2024)
This study investigated the effects of a dietary supplement containing lipids extracted from Altai wapiti antlers on patients with panic attacks (PA). Two groups of 30 patients aged 18-55 years were studied: the main group received the supplement, while the control group did not. Clinical effectiveness was assessed using questionnaires, adaptive response types, heart rate variability (HRV), and cytokine production. Results showed a significant decrease in PA manifestations, normalization of the autonomic nervous system function, and improved adaptive reactions in the main group. HRV analysis revealed a reduction in sympathetic tone and centralization of regulation processes. Hormonal status assessment indicated normalization of stimulated insulin and cortisol levels. The supplement also contributed to the normalization of spontaneous and PHA-stimulated production of IFNγ, IL-2, IL-4, and IL-1β cytokines, which play a crucial role in the interaction between the nervous and immune systems, ensuring stress resistance and body adaptation. During the 2-week follow-up, the main group experienced fewer and less severe PA episodes compared to the pre-treatment period. The study confirms the effectiveness of the dietary supplement in the prevention and treatment of PA, highlighting its multiple actions on stress resistance, autonomic nervous system function, stress-regulating hormones, and cytokine balance.